Comparative Analysis Between Objective Structured Clinical Examination (OSCE) and Conventional Examination (CE) As a Formative Evaluation Tool in Pediatrics in Semester Examination for Final MBBS Students - Mondal, R; Sarkar, S; Nandi, M; Hazra, A (Kathmandu University Medical Journal, 2012)
Background The use of objective structured clinical examination in pediatrics is not common in undergraduate evaluation process. Objective To evaluate the effectiveness of objective structured clinical examination as compare to conventional examination as formative assessment tool in Pediatrics. Methods We conducted a cross sectional comparative study in defined population of 9th semester MBBS students to evaluate the effectiveness of objective structured clinical examination as comparison to conventional examination as formative assessment tool in Pediatrics. We analyzed the perception of objective structured clinical examination among the students. Results Fifty-two students appeared for the objective structured clinical examination evaluation on the first day and 42 turned up for conventional examination on the next day. The 42 students who turned up for both examinations were asked to respond to the perception evaluation questionnaire. Comparison of the two examination styles showed that students fared better in objective structured clinical examination than in conventional examination both with respect to mean total score (p < 0.001) as well as mean percentage score. Out of the 42 subjects who appeared in both examinations, all passed in objective structured clinical examination and 35 passed in conventional examination – this difference was significant by McNemar’s chi-square test (p = 0.016). 73.8% of the students opined in favor of objective structured clinical examination as a better formative assessment tool whereas 9.5% students preferred conventional examination. Conclusions Objective structured clinical examination a statistically significant better evaluation tool with comparison to conventional examination. KATHMANDU UNIVERSITY MEDICAL JOURNAL VOL.10 | NO. 1 | ISSUE 37 | JAN - MAR 2012 | 62-65 DOI: http://dx.doi.org/10.3126/kumj.v10i1.6917